MOTIF MASYARAKAT MENABUNG DI CU TILUNG JAYA KABUPATEN PUTUSSIBAU - B01111119, ANGELA MARGARETHA ARIVINA (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACT CU Tilung Jaya is one of the cooperatives operating in the district Putussibau (Kapuas Hulu). CU Tilung Jaya offers a range of savings products to the public, namely DEPOSIT SHARES, SITILUNG SIMPARAAN, sympathetic, SITARUNA, Sintong, and SIPAJAR ,. The purpose of this study was to find out what the motives of members or customers in choosing to save in CU Tilung Jaya Putussibau. The population used in this study were all members of the CU Tilung Jaya Putussibau amounted to 21 093 people and is used as a sample as many as 50 people were supposed to represent. A questionnaire was used as a tool to collect data was then analyzed using descriptive analysis with percentages. The results showed that the characteristics of the members of the CU Tilung Jaya most respondents were clients of men, aged between 41-55 years, working as a merchant, had an average revenue per month above Rp. 2,000,000, and educated diploma. While the motive they save in CU Tilung Jaya is due to earn a profit sharing system, services, and credit facilities. Keywords: Motif member, CU Savings Tilung Jaya